2019
DOI: 10.20525/ijrbs.v8i6.488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inspirational Motivation on Employee Job Performance in the Insurance Industry in Kenya

Abstract: This study had two research questions as follows: What is the influence of inspirational motivation on employee job performance? To what extent does employee work value congruence moderate the relationship between transformational leadership and employee job performance? This study adopted the positivism research philosophy and correlation research design. The target population of the study was 676 lower-level managers from 52 insurance companies operating in Kenya as of 2017. A sample size of 245 was drawn us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…A similar study by Akeel (2014) sought to establish that the relationship between inspirational motivation and the performance of PHWs was found to be non-significant. Langat, Linge and Sikalieh (2019) equally investigated the effect of inspirational motivation on the job performance of PHWs and established that inspirational motivation significantly predicted the job performance of PHWs. Also, the findings agree with Mishra (2020), whose study established that all the four dimensions of transformational leadership, that is, idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration, yielded a positive and significant relationship with reliable organisational efforts, including the thrust to raise the performance of employees.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…A similar study by Akeel (2014) sought to establish that the relationship between inspirational motivation and the performance of PHWs was found to be non-significant. Langat, Linge and Sikalieh (2019) equally investigated the effect of inspirational motivation on the job performance of PHWs and established that inspirational motivation significantly predicted the job performance of PHWs. Also, the findings agree with Mishra (2020), whose study established that all the four dimensions of transformational leadership, that is, idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration, yielded a positive and significant relationship with reliable organisational efforts, including the thrust to raise the performance of employees.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Previous research found that work motivation has a positive and significant effect on work commitment (Melati et al, 2021;Marnisah et al, 2022;Lutfi et al, 2022, andBadrianto &Permatasari, 2022). In addition, the authors concluded that work motivation can improve employee performance in both the public and private sectors (Langat et al, 2019;Salim et al, 2023;Sutrisna, 2023;Tella & Ibinaiye, 2020;Apex-Apeh et al, 2020;Eliyana et al, 2020;Al-Jedaia &Mehrez, 2020, andSyamsir, 2020) In line with this, Prabowo & Yulianti (2022) concluded that employee work motivation is an important factor in consistently improving employee performance. The research provides inspiration or an overview of the importance of work motivation of construction service employees in synergizing with employee competency factors (visible and hidden competency).…”
Section: The Effect Of Work Motivation On Work Commitment and Employe...mentioning
confidence: 91%
“…Therefore, all employee efforts in achieving maximum work results can contribute to company performance in the long term. The results of research conducted by (Langat et al, 2019;Salim et al, 2023;Sutrisna, 2023;Tella & Ibinaiye, 2020;Apex-Apeh et al, 2020;Eliyana et al, 2020;Al-Jedaia & Mehrez, 2020;and Syamsir, 2020) show that work motivation directly has a significant effect on employee performance. For example, the results of research (Prabowo & Yulianti, 2022) concluded that employee work motivation is a critical factor in consistently improving employee performance.…”
Section: Work Motivation and Employee Performancementioning
confidence: 98%
“…Organizations need to develop skills that enable leaders to operate in uncertain environments according to Mugisha and Berg (2017). Bennett et al (2016) found the need to develop a sense of positive identity, acceptance of uncertainty, effective sense-making, learning agility and relevant leadership practices for uncertain times Several studies on different leadership styles and their impact on organizational performance were reviewed including those by Wachaga (2017), Kabogo & Deya (2020), Langat (2019) and Linge and Sikalieh (2019). However, the researcher noted limited research on adaptive leadership generally or adaptive leadership and performance and specifically, in the context of the insurance industry.…”
Section: Statement Of the Problemmentioning
confidence: 99%